Impulse Pressuring Diffusion Bonding of Titanium to Stainless Steel Using a Copper Interlayer. Issue 5 (May 2015) - Yongqiang, Deng; Guangmin, Sheng; Lijing, Yin
Abstract Impulse pressuring diffusion bonding of commercially pure titanium to 1Cr18Ni9 stainless steel was carried out using a copper interlayer in an attempt to reduce the bonding time and alleviate the detrimental effect of interfacial reaction products on bonding strength. Successful bonding has been achieved at 850 °C under a pulsed pressure of 8∼20 MPa within a duration of only 120∼180 s, which is notably shortened in comparison with conventional diffusion bonding. Microstructure characterization revealed that a sequence of Ti-Cu intermetallic compounds were formed at the Ti/Cu interface and the Cu/stainless steel interface was characterized by the presence of solid solution of Cu in γ Fe without any interfacial reaction products. Maximum bonding strength of 346 MPa was obtained when the joint was bonded for 120 s. Upon tensile loading, the joints fractured along the Ti/Cu interfacial reaction layer in a brittle cleavage manner, indicating that the impulse pressuring diffusion bonding can alleviate the harmful influence of interfacial intermetallic compounds on joint performances to a certain extent, but it is infeasible in completely eliminating the negative effect of the brittle intermetallic compounds.